Georgia O'Keeffe's "Black Place". Issue 3 (3rd July 2019) - Scott, Sascha T.
Abstract : During World War II, Georgia O'Keeffe created a series of foreboding paintings of New Mexico's Bisti Badlands, which she named the "Black Place." Produced within a wartime image ecosystem in which photographs, films, and cartography vividly communicated the power of air war to obliterate humanity and nature, O'Keeffe's "Black Place" series grappled with the war's destruction and shifts in perceptions of time, distance, and place. In its tense engagement with a new technological and visual world, the Black Place series finds kindship with the art of the bourgeoning generation of Abstract Expressionists.